PENGARUH PEMBERDAYAAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN KOTA BANDA ACEH: THE EFFECT OF EMPOWERMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE PUBLIC HOUSING AND RESIDENTIAL AREAS SERVICE OF BANDA ACEH CITY - Muhammad bayhaqqi; Erlinda; Mahyuddin (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
This study aims to analyze the influence of empowerment and work motivation on employee performance at the Department of Public Housing and Settlement Areas of Banda Aceh City. The research method employed was quantitative with a census approach involving the entire population of 46 civil servants. Data were collected through a closed-ended questionnaire and analyzed using multiple linear regression. The findings indicate that empowerment has a positive and significant effect on employee performance, with a regression coefficient of 0.316. Work motivation also shows a positive and significant effect, with a regression coefficient of 0.427, indicating that work motivation is the dominant factor in improving employee performance. The correlation coefficient (R) of 0.779 demonstrates a strong relationship between empowerment and work motivation simultaneously on performance. Meanwhile, the coefficient of determination (R²) of 0.589 shows that 58.9% of the variation in employee performance is explained by these two variables, while the remainder is influenced by other factors. These findings suggest that strategies to improve employee performance should integrate both work motivation and empowerment in a balanced manner. Practically, organizational leaders should develop policies that include training programs, delegation of authority, recognition of achievements, and the creation of a conducive work environment. This holistic approach is expected to encourage creativity, innovation, and productivity, thereby supporting the achievement of organizational goals effectively and efficiently.